Pengaruh Etika Pelayanan Publik Terhadap Kepuasan Masyarakat di Kelurahan Pau Kabupaten Manggarai - Aurelia Noveyr Ledya Diaz; Ni Putu Anik Prabawatib; I Putu Dharmanu Yudartha (CV. Lenggogeni Data Publishing, 2023)
Services provided to the public (community) with good ethics will bring satisfaction to service users. Public service ethics is one of the elements that greatly determines the satisfaction of the public served as well as the success of the public service organization itself. The purpose of this study was to determine the effect of public service ethics on community satisfaction in Pau Village, Manggarai Regency. This research was conducted using a quantitative research method which aims to determine the effect of public service ethics (variable X) on community satisfaction (variable Y) in Pau Village, Manggarai Regency using a correlation approach. The primary data of this study are the people of Pau Village with a sampling of 100 respondents. The results showed that public service ethics had a positive and significant effect on community satisfaction in Pau Village with an R2 result of 0.780, this means that community satisfaction was influenced by public service ethics by 78%. The results of simple linear regression calculations show that every 1% increase in the public service ethics of Pau Village, Manggarai Regency, will increase community satisfaction by 57.2%. Based on the results of the significance test, the tcount of 18.614 is greater than the ttable (1.987) with a significance level of 0.000, this shows that public service ethics has a positive and significant effect on community satisfaction in Pau Village, Manggarai Regency.